The eco‐friendly burger: Could cultured meat improve the environmental sustainability of meat products? - Tuomisto, Hanna L (EMBO Rep, 2018)
Cultured meat, produced in vitro from stem cells, could address the growing demand for meat and fish products. But the technology is not ripe enough to become a sustainable alternative to livestock. [Image: see text]